Telehealth coaching in older adults, behavior change, and impacts of the COVID-19 pandemic: analyses from The Brain Health Champion Study - McFeeley, Brittany; Nicastri, Casey; Krivanek, Taylor; Daffner, Kirk R.; Gale, Seth A. (Frontiers in Digital Health, 2025)
IntroductionWhen COVID-19 containment strategies were imposed in March 2020, we became interested in how these restrictions might interfere with brain-healthy behaviors of older adults who were either actively participating in or who had recently completed our telehealth behavior change intervention. Telehealth interventions have emerged as important tools for supporting brain health behaviors remotely, particularly among older adults. The objective of the current study was to assess how older adults with and without cognitive impairment were affected by COVID-19 restrictions and whether they were affected differently based on their active participation or recent completion of our Brain Health Champion (BHC) study and their cognitive status.MethodsBHC study 1.0 and 2.0 participants and their study partners were emailed in April and May of 2020 a link to five electronic surveys to collect qualitative and quantitative data on various health factors, including self-reports of pre-pandemic and current brain health behaviors (e.g., physical activity, Mediterranean diet adherence, social engagement, and cognitive stimulation), anxiety, sleep, and depression. The fifth survey was distributed to collect study feedback.ResultsTen out of 11 participants from Study 2.0 and 15 out of 30 participants from Study 1.0 completed the surveys. Results demonstrated that early pandemic restrictions negatively impacted all participants in physical activity (p < .01) and social interactions (p < .001), with no impact on cognitive activities (p = .479) and dietary intake (p = .814). A significant difference was found between Study 1.0 and 2.0 participants (p < .001) in self-reported changes in level of cognitive activity. Study 1.0 participants indicated a decrease in cognitive activities since the start of COVID-19 restrictions, whereas those in Study 2.0 reported an increase in cognitive activities.DiscussionOur findings suggest that pandemic restrictions significantly impacted activities typically done outside the home (social and physical activity), while those feasibly achieved at home were less affected (Mediterranean diet adherence and cognitive activity). Additionally, the intervention augmented by digital health components likely exerted some protective effects against the impact of COVID-19 containment strategies. Digitally-facilitated research and clinical telehealth programs are well-positioned to offer some protection to vulnerable individuals from disruptive events that could impede adoption or maintenance of healthy lifestyle changes.